Bench v Bar: Contempt of Court and the New Zealand Legal Profession in Gillon v MacDonald (1878) - Morris, Grant (Victoria University of Wellington Law Review, 2010)
Gillon v MacDonald (1878) was the climax of a feud that caused division in, and undermined the reputation of, the early New Zealand legal profession. Gillon features one of the most controversial episodes of contempt of court by a barrister in colonial legal history. The nature of the New Zealand legal profession, and in particular the relationship between bench and bar, is exposed through the case, its prologue and its aftermath. The complex saga occurred over several years and involved all three branches of government. Its causes are open to debate, but this article argues that personal and professional rivalry lies at the heart of the saga, and in particular, an obsessive vendetta on the part of George Elliot Barton. The events described in this article had far reaching consequences including possibly influencing New Zealand’s most infamous legal decision, Wi Parata v Bishop of Wellington (1877).